Developing a System to Assure the Quality of ICT Learning Materials to Enhance Lifelong Learning - Sambrook, Sally; Geertshuis, Susan; Cheseldine, David; Willis, Rob (Proceedings of the International Conference on Networked Learning, 2000)
This paper reports on a research project that aims to develop a system for identifying 'quality' computer based learning materials. Hence, the research is of an applied nature. Computer based learning materials, those using information and communication technology (ICT), are defined as encompassing both 'online' (web-based) or 'stand alone' (CDROM) products. The purpose of this research is to design a comprehensive yet flexible system providing a series of evaluation tools and information to assist users judge the quality of these products. This project, one of a suite of interrelated projects, focuses on the pedagogical quality of computer based learning materials.